2023
DOI: 10.1111/idh.12723
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of YouTube videos as a source of information about dentin hypersensitivity

Özlem Saraç Atagün,
Seval Ceylan Şen,
Tuğçe Paksoy

Abstract: ObjectivesEven though tooth sensitivity is a prevalent dental issue today, more information is available to patients via social media concerning the subject. This study aimed to examine what patients may learn about tooth sensitivity from online videos on YouTube™ and evaluate the accuracy of the information given.MethodsIn this cross‐sectional investigation, two experienced periodontologists used the keyword ‘tooth sensitivity’ to conduct an organized search into YouTube videos containing knowledge regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
(62 reference statements)
2
5
0
Order By: Relevance
“…Previous studies have reported that 75% of videos on oral leukoplakia were created by independent users and company advertisements, 65% of videos on orthodontic pain were created by laypersons, and 36.7% of videos on dentin hypersensitivity were created by healthcare professionals [ 23 , 25 , 26 ]. In this study, 65.1% of the included videos were posted by healthcare professionals, and 10.9% were posted by hospitals and universities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have reported that 75% of videos on oral leukoplakia were created by independent users and company advertisements, 65% of videos on orthodontic pain were created by laypersons, and 36.7% of videos on dentin hypersensitivity were created by healthcare professionals [ 23 , 25 , 26 ]. In this study, 65.1% of the included videos were posted by healthcare professionals, and 10.9% were posted by hospitals and universities.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a positive significant correlation was found between video duration, number of comments, interaction index and total DISCERN scores, total content scores, and total DISCERN scores and GQS values. Saraç Atagün et al stated that quality and reliable videos with rich content have a longer duration and receive more comments [ 23 ]. Since these videos are more informative, it is expected that they will receive more comments and have a higher interaction index.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While evaluations of YouTube™ videos have been conducted on various dentistry-related topics such as dentine hypersensitivity, vital pulp capping, gummy smile surgical treatment, and sinus lifting surgery [ 17 , 20 - 22 ], there has been no study evaluating the information quality of YouTube™ videos on NG. Despite using appropriate search terms, both physicians and patients encounter difficulties in obtaining relevant information due to redundant content.…”
Section: Discussionmentioning
confidence: 99%